Checkpoint inhibitors in chronic kidney failure and an organ transplant recipient. (November 2016) - Herz, Saskia; Höfer, Thomas; Papapanagiotou, Matina; Leyh, Julia Christina; Meyenburg, Sarah; Schadendorf, Dirk; Ugurel, Selma; Roesch, Alexander; Livingstone, Elisabeth; Schilling, Bastian; Franklin, Cindy
Abstract: Background: Immune-checkpoint inhibitors have been approved for the treatment of metastatic melanoma based on several phase III trials. Patients after organ transplantation and patients with impaired renal function were excluded from these studies. Recently, allograft rejections were reported in organ transplant recipients receiving PD-1 blocking antibodies. Patients and findings: Four patients with metastatic melanoma and impaired kidney function (baseline serum creatinine 1.79–2.59 mg/dl) were treated with immune-checkpoint blockers, of which one was a kidney-transplant recipient receiving immunosuppressive therapy with tacrolimus and prednisolone. The patient was initially treated with the anti-CTLA-4 antibody ipilimumab after detailed explanation of the potential risk of allograft rejection. Upon disease progression, therapy was switched to the anti-PD-1 antibody nivolumab. The other three patients were treated with nivolumab or pembrolizumab, two of them after previous therapy with ipilimumab. Results: The patients received a median of six doses (range 3–21) of anti-PD-1 antibodies and 3–4 doses of ipilimumab. Kidney function tests remained stable throughout the course of checkpoint blockade. In the kidney transplant recipient, neither ipilimumab nor nivolumab led to an allograft rejection. Responses to anti-PD-1 treatment were divergent with two patients showing disease progression, one achieving a mixed response and one experiencing a complete response. Conclusion: These cases show that checkpoint inhibitors can be a safe therapeutic option in patients with impaired kidney function. Furthermore, we report the first organ transplant patient with malignant melanoma who received ipilimumab followed by nivolumab without experiencing a kidney allograft rejection. Highlights: CTLA-4 and PD-1 blockade was safe in melanoma patients with impaired renal function. No unexpected toxicity of CTLA-4 and PD-1 blockade was observed. PD-1 blockade showed activity in melanoma patients with impaired kidney function. Nivolumab did not lead to allograft rejection in a kidney transplant recipient.